Performance Comparison of Wavefront-Sensorless Adaptive Optics Systems by Using of the Focal Plane - Huizhen Yang; Zhen Zhang; Jian Wu (International Journal of Optics)
The correction capability and the convergence speed of the wavefront-sensorless adaptive optics (AO) system are compared based on two different system control algorithms, which both use the information of focal plane. The first algorithm is designed through the linear relationship between the second moment of the aberration gradients and the masked far-field intensity distribution and the second is stochastic parallel gradient descent (SPGD), which is the most commonly used algorithm in wavefront-sensorless AO systems. A wavefront-sensorless AO model is established with a 61-element deformable mirror (DM) and a CCD. Performance of the two control algorithms is investigated and compared through correcting different wavefront aberrations. Results show that the correction ability of AO system based on the proposed control algorithm is obviously better than that of AO system based on SPGD algorithm when the wavefront aberrations increase. The time needed by the proposed control algorithm is much less than that of SPGD when the AO system achieves similar correction results. Additionally, the convergence speed of the proposed control algorithm is independent of the turbulence strength while the number of intensity measurements needed by SPGD increases as the turbulence strength magnifies.